Hubungan Kecanduan Game Online dengan Manajemen Waktu pada Mahasiswa Fakultas Kedokteran Universitas Lampung - Ahmad Mufid NA; Dwita Oktaria; Arif Yudho Prabowo; Oktafany (MAJORITY, 2020)
Online games are a phenomenon that young people are interested, including students. Not a few of them have entered the stage of online game addiction. It can interfere with or decrease the ability of students to carry out time management. This study aims to determine the relationship between online game addiction and time management in 2015 students from Faculty of Medicine Universitas Lampung. This study uses a cross sectional approach. The research sample was taken as many as 162 respondents and asked to fill out two questionnaires namely Game Addiction Scale for Adolescents and Time Management “Effective Learning Service”. Based on the results of univariate analysis as many as 27,8% of students experience online game addiction and as many as 40,1% of students with enough time management level categories. Based on bivariate analysis using chi square test found a significant relationship between online game addiction and time management with a value of p=0,001 (p